PENGARUH PENDEKATAN PEMBELAJARAN KOOPERATIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Ika Sartika (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
This study aims to determine the influence of critical thinking skills among students who received mathematics learning through cooperative approaches with students who received conventional math learning. This research is a quasi-experimental study in junior high Madya Medan city, with the subject of student population is 31 and Junior Secondary Schools Private Nurul Hasanah and take 2 classes each of which is in Junior High School 31 class VIII.3 and VIII.4 while in junior high Private Nurul VIII.1 and VIII.2 Hasanah class as a research sample. Samples were randomly selected from two school units for the entire eighth grade at Junior High School 31 there are 5 classes in junior high while Private Nurul Hasanah there are 5 classes. The instrument used to collect data in this study consisted of testing the ability to think critically before the instruments used first tested and the results of high reliability critical thinking (0.61). From the research there is the influence of critical thinking skills to obtain cooperative learning with students who obtain conventional learning. For the ability to think critically, to analyze the experimental class question 0.86 (high) while the control class 0.84 (high), 0.84 synthesize experimental class question (high) while the control class 0.80 (high), recognize the problem experimental class 0 , 86 (high) while the control class 0.77 (high), problem-solving experimental class 0.88 (high) while the control class 0.86 (high), concluded an experimental class question 0.91 (high) while the control class 0, 83 (high). From the results of this study concluded that critical thinking skills in students who obtained a cooperative learning approach to change significantly better than students who received conventional learning. The cooperative learning approach is an alternative for teachers of mathematics in presenting math, it should be socialized cooperative learning approach used in institutions of units of each school.